A 3D imaging technique for circular radar sensor networks based on radon transform. (1st August 2013) - Zhang, Biao; Pi, Yiming
A three dimensional (3D) imaging method which is a complex–valued generalised Radon transform (CGRT)–CLEAN algorithm for circular radar sensor networks (CRSN) is proposed in this paper. Based on the analysis of CRSN echo model, the echo of a scatterer in the range–azimuth domain can be modelled as a single cycle sinusoid. Inspired by the generalised Radon transform, this paper utilises the CGRT to estimate for scatterers' positions. Then, combining the CGRT with CLEAN technique, the parameters of a scatterer which include position information and reflection coefficient can be obtained. Thus, a 3D image of a target can also be reconstructed. Comparing with other algorithms, the outstanding characteristic of the proposed algorithm is that there is no need to analyse azimuth spectrum to achieve a 3D imaging. The performances of the CGRT–CLEAN method have been verified by simulations, and the results confirm the effectiveness of the proposed algorithm for processing CRSN data.